2015
DOI: 10.18357/ijcyfs.62201513501
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Disconnection: Child Care Policies in Changing Economic Times in the Canadian Context

Abstract: This article brings together findings from two studies that focus on child care in Canada. The first maps the coverage of child care over the first decade of the 21st century in four Canadian daily newspapers. It shows that the voices of children, mothers, and child care providers are virtually absent from policy discussions. The second study, which remedies the parental invisibility identified by the first study, relies on interviews with mothers of young children in two jurisdictions with distinctive approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…As Friendly (2000) states "the labour force participation rate of Canadian women with children aged zero to six has been above 65 per cent for some years" (p.6). Albanese and Rauhala (2015) coincide with this idea stating that "as a result [of the UCCB] in most of the country child spaces remain expensive, in short supply, and are perceived, Can Canadian Women Have it All? both privately and publicly as the individual responsibility of parents" (p. 257).…”
Section: Federal Government Assistancementioning
confidence: 91%
See 1 more Smart Citation
“…As Friendly (2000) states "the labour force participation rate of Canadian women with children aged zero to six has been above 65 per cent for some years" (p.6). Albanese and Rauhala (2015) coincide with this idea stating that "as a result [of the UCCB] in most of the country child spaces remain expensive, in short supply, and are perceived, Can Canadian Women Have it All? both privately and publicly as the individual responsibility of parents" (p. 257).…”
Section: Federal Government Assistancementioning
confidence: 91%
“…In essence, it is the most inclusive child care policy in Canada. Albanese and Rauhala (2015) found that Quebec women's labour force participation rates, which were below the national average in 1976, had surpassed the average by 2005. Additionally, Ferns and Friendly (2014) found that Quebecois parents were paying the lowest daycare fees in the country (Albanese & Rauhala, 2015, p. 255).…”
Section: Quebec -A Leading Province In Child Care Reformmentioning
confidence: 96%
“…While quoting parents may be seen as a progressive, bottom-up approach to policy input, it could be argued that such an approach to reporting occludes the policy-level perspective in which childcare advocates and experts are intimately familiar. Most recently Albanese & Rauhala (2015) merged findings from their ongoing study of newspapers between 2000 and 2007 and qualitative interviews with mothers in rural Ontario and Quebec. The authors note an overall absence of mother's voices in newspaper articles (instead observing the gender neutral terms such as "parents" and/or "families") alongside observations from interviews that mothers experience significant, daily "stress and frustration" due to a lack of high quality, accessible childcare services (Albanese & Rauhala, 2015).…”
Section: Literature Review: Childcare Policy Representation In the Canadian Pressmentioning
confidence: 99%
“…Canadian mothers continue to cope with the ongoing "stress" and "frustration" of having little support to engage in both paid work and unpaid social reproductive work (Albanese & Rauhala, 2015). During the era of Harper's Conservative government, pan-Canadian "childcare" 3 policy was limited to the Universal Child Care Benefit (UCCB)a taxable $100 (later $160) per month payable directly to parents for each child under the age of 6.…”
Section: Chapter 1: Introductionmentioning
confidence: 99%
“…For example, daycare in most countries has become increasingly subject to market forces and is therefore not available to modest and low-income households. Albanese and Rauhala (2015) argue that children, mothers, and child care providers tend to be missing from public policy discussions about daycare. Yet, high quality child care is critical to healthy child development and children's readiness to learn when they begin school.…”
Section: Public Policy and Public Policy Change As Determinants Of Chmentioning
confidence: 99%